An Assessment of the Potential Capability of Banks in the United Kingdom Banks to Exploit Sociodemographic Change - Chaston, Ian (2009)
The purpose of the paper is to examine whether UK banks recognize that population ageing and the increasing wealth the over-50 age group, relative to younger people in the 18-49 year age group, mean the older consumer offers an increasingly important target market to sustain business performance. A mail survey was undertaken of UK bank employees. The survey tool utilized previously validated scales to assess entrepreneurial orientation, strategic flexibility, and organizational competence. Results suggest that, when compared to an earlier study of other financial service providers, branchlevel employees perceive that their banks lack entrepreneurial orientation and strategic flexibility. The implication is the ability of these banks to exploit the opportunity to generate incremental revenue from focusing upon the marketing of services to people over 50 may be somewhat restricted. The survey does indicate, however, that UK banks have the necessary internal capabilities in areas such as human resource management (HRM), service quality, and information management to effectively service the needs of older consumers. Future research is required concerning the motivations of the management within UK banks who have apparently yet to recognize the opportunities available by focusing greater emphasis on the provision of services to older people.